Administrative control of mobile phone company licensing contracts (A comparative study) - omair sahi, Alham; faleh al ahmadi, Assist. prof. Ansam (Basra studies journal, 2022)
Administrative control of the most important themes that affect the organizational entity to the States currently present, it is necessary to protect the public facilities by detecting the problems and the development of appropriate solutions to treat them and to stand as well as the extent of the administration's excellence, the achievement of the goals of the public facilities, including the facility of the publications, the application of the laws and the guidance of the public money and the reservation of the public money and the revolution of the public money and the revolution of the public money and the extent of the publication of the public and the revolution of the public money and the extent of the public money and the extent of the publication of the public and the revolution of the total money and the extent of the corruption of the public and the revolution of the total money and the extent of the corruption of the mobile phone to correct the michaelch of the above-mentioned items. The two parts of the research The two-way teams The most important Control of the administration of the mobile contractor is not contracting on the contract contracts for mobile phone.